HUBUNGAN ANTARA SERVICESCAPE DENGAN KEPUASAN PELANGGAN FARMASI RSUD KOTA BOGOR - ., Mujito (Economicus, 2019)
The purpose of this study was to find out and analyze the influence of ambient condition, design factor, and social factors, together on the customer satisfaction of Bogor City Hospital. This research will be conducted at the Regional General Hospital (RSUD) of Bogor City. The population of this study was the Pharmacy patients of RSUD Kota Bogor, with the condition of patients who had more than twice or more treated and took drugs in the Pharmacy Installation of RSUD Kota Bogor, namely as many as 340 In this study the number of samples taken amounted to 184 with Slovin formula. Data analysis using linear regression with the help of the SPSS program. The results showed (1) there was a positive and significant ambient condition effect on customer satisfaction with the value of t calculated ambient condition = 2.176 greater than the value of t table 1.972, with a significance value of 0.031 <0.05. (2) There is a positive and significant influence of the design factor on customer satisfaction with the value of t calculated design variable factor = 11.255 greater than the value of t table 1.972, with a significance value of 0.000 <0.05 (3) There is a positive and significant social factor variable on customer satisfaction with the value of t counted social factor variable = 7.466 greater than the value of t table 1.972, with a significance value of 0.000 <0.05. (4) There is a positive and significant influence of variable conditions, design factors, and social factors together on customer satisfaction with a calculated F value of 48,493> F table 2,653.